2013
DOI: 10.1016/j.algal.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Pilot plant testing of continuous hydrothermal liquefaction of microalgae

Abstract: We describe a pilot plant for continuous hydrothermal processing of biomass. Results were obtained for two microalgae strains, Chlorella and Spirulina, across a range of biomass loadings (1-10 wt%), temperatures (250-350 °C), residence times (3-5 minutes) and pressures (150-200 bar). Overall, the biocrude yields were found to increase with higher biomass loading, higher temperature and longer residence time. More severe reaction conditions also reduced the oxygen content of the bio-crude, while the nitrogen co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
169
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(190 citation statements)
references
References 24 publications
12
169
1
8
Order By: Relevance
“…Reducing particle size from 600 to 60 μm for sweet sorghum can increase ethanol yields by a factor of two for solid substrate fermentation (SSF) [26]. HTL Particle size has a direct correlation to pumpability and pressure control [27,28]. Particle size has a minimal effect on heat transfer in liquid water but smaller particles will show a slight decrease in solid residue (14-7 %) for mixtures of perennial grasses at 374°C and 22.1 MPa [29].…”
Section: Pyrolysismentioning
confidence: 99%
“…Reducing particle size from 600 to 60 μm for sweet sorghum can increase ethanol yields by a factor of two for solid substrate fermentation (SSF) [26]. HTL Particle size has a direct correlation to pumpability and pressure control [27,28]. Particle size has a minimal effect on heat transfer in liquid water but smaller particles will show a slight decrease in solid residue (14-7 %) for mixtures of perennial grasses at 374°C and 22.1 MPa [29].…”
Section: Pyrolysismentioning
confidence: 99%
“…29−32 Additionally, continuous-flow HTL processes have exclusively investigated the use of microalgae and lignocellulosics. 12,26,33,34 However, no information on continuous-flow HTL with filamentous fungi has been reported. This study aimed to determine the feasibility of using fungal biomass as an HTL feedstock.…”
Section: Introductionmentioning
confidence: 99%
“…For C. vulgaris and A. platensis in a continuous reactor [30] it was also shown that at 250 °C with 3 min residence time the structure of Chlorella cell wall was still given but to a great extent not functional anymore. At temperatures of 275 °C and 300 °C the structure of the cell wall itself was destroyed.…”
Section: Discussionmentioning
confidence: 99%